Jurisdiction and arbitration clauses in the contract of carriage of goods by sea : the Nigerian practice - Magashi, Awwal Ilyas (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2017)
In every commercial undertaking, disputes are bound to emerge and identifying in advance as well as putting strong mechanism on how best to resolve those disputes will go a long way in enhancing commercial dealings and provides the much needed certainty. From the perspective of contract of carriage of goods by sea, dispute resolution clauses in a form of jurisdiction and arbitration clauses are normally incorporated into a bill of lading with a view to providing a guideline on how those disputes could be resolved in a more efficient and best way possible. At the moment, with the exception of the New York Convention, 1958, there is no legal regime accepted globally, which is poised at regulating jurisdiction and arbitration clauses in the contract of carriage. This lack of uniformity and integration led to the emergence of various local legislative enactments vis-à-vis hybrid regimes, which open a Pandora Box of problems such as lis-alibi pendens, forum shopping, non-recognition and enforcement of foreign judgment or award. It is against this background this research undertakes a voyage to examining the practice in Nigeria pertaining to jurisdiction and arbitration clauses in a contract of carriage of goods governed by a bill of lading with a view to ascertaining whether the Nigerian practice is in tandem with International Best Practice (IBP). In so doing, this research specifically devotes itself with the Nigerian practice towards these clauses albeit taking into consideration the practices in some selected jurisdictions to wit: United States of America (USA); United Kingdom (UK); The European Union (EU); and New Zealand. The rationale behind looking at the practices in those jurisdictions was not for the purpose of making a comparative analysis but with a view to borrowing a leaf on how to adopt an International Best Practice (IBP). In order to carry out the research in an efficient manner, two methodologies were adopted: doctrinal and non-doctrinal. For the former, the research examines some of the relevant legislation as well as some selected judicial authorities dealing with jurisdiction and arbitration clauses in the contract of carriage. For the latter, an unstructured interview was conducted where opinions of the key players in the Nigerian maritime industry were sought concerning the practice of the Nigerian practice. The research findings demonstrate that the Nigerian practice is a far away from an International Best Practice as it has only succeeded in exacerbating the misery of the Nigerian consignee. This is especially when he attempts to enforce a Nigerian judgment or award obtained in breach of either jurisdiction or arbitration clause in a contract of carriage in a foreign country. It further reveals that Nigeria as a party to the New York Convention breaches its treaty obligation to observe and enforce the observance of party autonomy to freely agree on where to arbitrate their disputes. The consequence of this practice left the Nigerian consignee with a barren judgment or award, which bears no fruit thereby forcing him to agree to settle the matter out of court for a very token fee. The research recommends that a more holistic approach should be embraced by adopting new proposed draft legislation, which is in conformity with an International Best Practice.